Estimasi Tingkat Pengangguran Terbuka di Provinsi Jambi dengan Metode Double Exponential Smoothing - Anisa Rahmawati; Nayla Desviona; Tiara Puapita Sari (NUCLEUS, 2022)
Unemployment is an employment problem that is often faced in every region, especially in Jambi Province.  The indicator used to determine the number of unemployed is the open unemployment rate (TPT).  High unemployment can be a major source of poverty that can lead to crime and hinder the process of economic development.  As an initial precaution for the government before the increase in unemployment, which is to estimate the future TPT in Jambi Province.  One of the methods used in estimating TPT in Jambi Province is the Double Exponential Smoothing Method from Holt.  The measure of the forecast error uses the Mean Absolute Percent Error (MAPE).  The aim is to obtain estimated TPT results in Jambi Province in the coming year, using Holt's Double Exponential Smoothing Method.  The estimation results obtained, for TPT data there is a MAPE value of 18.96% with parameters  = 0.9 and  = 0.2.  The estimation model obtained is = .  The estimation results show that the TPT rate will continue to increase next year, it can be taken into consideration for the government in determining future plans to reduce TPT in order to accelerate economic development in Jambi Province.